Employing the dimensions of value-based leadership in activating organizational semiotics: a proposed management model / Jinan Shihab Ahmed - Ahmed, Jinan Shihab (Research Management Institute (RMI), 2022)
The study aims to know the effect of value-based leadership on organizational semiotics at Al-Mustaqbal University College, Iraq. A sample of 115 respondents, selected from the rank of the university lecturers and professors, was administered a self-report questionnaire. The data thus gathered were analyzed using both descriptive and inferential statistical tools available in SPSS. The results showed a significant positive correlation between value-based leadership and organizational semiotics. Similarly, the results confirm the existence of a positive impact of value-based leadership and organizational semiotics. The study reached concludes that administrative leaders in private colleges exhibit value-based leadership characteristics, anticipate the future and work hard and persistently to realize it, and also possess sound entrepreneurial dispositions. However, the study discovered that need more motivating and inspiring that could enable them to be more creative and innovative. Thus, there is a need for Al-Mustaqbal University College to pay more attention to these psychological needs of employees. Additionally, attention should be invested in developing university leaders' competencies in risk-taking, proactiveness, and creativity.